Variation in the strength and softness of selection on deleterious mutations. - Laffafian, A.; King, J.D.; Agrawal, A.F. (Evolution, 2010)
Deleterious alleles constantly enter populations through mutation. Understanding the nature of selection against such alleles is required to assess their impact on populations. In a subdivided population, two distinct aspects of selection are important: the strength and softness of selection. Using Drosophila melanogaster, we estimated both aspects of selection for each of eight loci across two environments. These data allow us to test conflicting predictions about the factors affecting the softness of selection. First, we show that the softness of selection is not determined by ecological conditions alone. Second, we find that resource limitation makes selection stronger but does not make it softer. Third, we find that wild-type individuals tend to benefit more than mutants from being reared with competitors of low genetic quality. This means that selection is effectively "harder" on mutants than wild types. A model is presented showing that the sensitivities of mutants and wild types to local competitors differentially affect equilibrium mutation frequency and measures of load.